From Rise to Fall: The Axiological Dimension of the Putin Era (Politeja, 2019)
Based on the 2000–2018 comparative studies of the Institute of Sociology of the Russian Academy of Sciences and the Russian Public Opinion Research Center (VTsIOM), the author presents the process of transition of the “Putin era” from the stage of consolidation built upon public consensus achieved at the beginning of the “zero” (нулевых) years to the current stage of value crisis that arose in 2012–14 and lasts to this day. Although the current state of society canno tbe unequivocally interpreted as a split, contradictions in the system of values are growing. Implementation of the idea of a strong state is delegated to social groups that are least modernized. Moreover, within the state itself, frustration has been growing among the whole society. The increasing demand for change has not yet been materialized in the form of any political “body”, which makes the inevitable transit of epochs extremely risky for the country and the society.